L'engendrement des choses: des hommes, des femmes et des techniques - Chabaud-Rychter, Danielle; Gardey, Delphine (Histoire des sciences, des techniques et de la médecine, 2002)
"Le monde contemporain est marqué par une amplification des biens et des choses, des techniques et des artefacts ; toutes choses nous semblant à la fois ordinaires, évidentes et neutres. Cette modernité est rarement interrogée du point de vue des hommes et des femmes qui la vivent. Pourquoi en effet prêter des intentions aux choses? Elles participent de nos vies, pourvoient à nos besoins, nous soulagent de bien des tâches. Remettre en question la neutralité des techniques est pourtant une bonne façon de s'interroger sur les rapports sociaux de sexes, en se demandant pourquoi les femmes sont durablement exclues de certains domaines techniques ; quel pouvoir confère la maîtrise des techniques ; quel est l'enjeu politique et symbolique de cette maîtrise ; et, au bout du compte, comment les techniques contribuent à ordonner le social, et en particulier les relations sexuées."
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; france; inégalités; postmodernisme; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

Climate change vulnerability, impacts, and adaptation: Why does gender matter? - Denton, Fatma (Gender & Development, 2002)
Gender-related inequalities are pervasive in the developing world. Although women account for almost 80 per cent of the agricultural sector in Africa, they remain vulnerable and poor. Seventy per cent of the 1.3 billion people in the developing world living below the threshold of poverty are women. It is important that the consequences of climate change should not lead already marginalised sections of communities into further deprivation. But key development issues have been at best sidetracked, and at worst blatantly omitted, from policy debates on climate change. The threats posed by global warming have failed to impress on policy-makers the importance of placing women at the heart of their vision of sustainable development. This article argues that if climate change policy is about ensuring a sustainable future by combining development and environment issues, it must take into account the interests of all stakeholders. The Global Environment Facility and the Clean Development Mechanism of the Kyoto Protocol can play a role in ensuring sustainable development, provided they are implemented in a way that does not disadvantage women and the poor.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; changements climatiques; discipline; environnement; projet charge mentale; périodes historiques; santé; science politique; science politique et droit; thématiques

Life during wartime: Emotions and the development of act up - Gould, Deborah (Mobilization: An International Journal, 2002)
Focusing on the street AIDS activist movement ACT UP, this article explores the question of social movement sustainability. Emotions figure centrally in two ways. First, I argue that the emotion work of movements, largely ignored by scholars, is vital to their ability to develop and thrive over time. I investigate the ways AIDS activists nourished and extended an “emotional common sense” that was amenable to their brand of street activism, exploring, for example, the ways in which ACT UP marshaled grief and tethered it to anger; reoriented the object of gay pride away from community stoicism and toward gay sexual difference and militant activism; transformed the subject and object of shame from gay shame about homosexuality to government shame about its negligent response to AIDS; and gave birth to a new “queer” identity that joined the new emotional common sense, militant politics, and sexradicalism into a compelling package that helped to sustain the movement. Second, I investigate the emotions generated in the heat of the action that also helped the street AIDS activist movement flourish into the early 1990s.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; VIH; amériques; approches et analyses; identités LGBTQIA2+; militance; mouvements sociaux; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; émotions; états-unis

Femmes, violences et espace public: une réflexion sur les politiques de sécurité - Lieber, Marylène (Lien social et Politiques, 2002)
Lorsqu'on se penche sur les politiques publiques concernant les violences en France, on relève une division des compétences entre les politiques dites « de sécurité » et les politiques « contre les violences faites aux femmes ». On constate que les politiques de sécurité, en se basant sur les statistiques de criminalité et de victimation, portent essentiellement sur l'espace public et marginalisent les violences faites aux femmes dans l'espace privé. Pour autant, elles ne prennent pas non plus en considération les violences perpétrées à leur encontre dans l'espace public. Or, divers exemples venant de pays étrangers esquissent des réponses faites par les pouvoirs publics à ces violences
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; droits des femmes*; europe; france; histoire et politique; pol4102; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; sécurité; thématiques; violences